THE PROBLEM OF INCREASING STUDENTS' MOTIVATION TO PARTICIPATE IN PHYSICAL EDUCATION AND SPORTS - Beysenova Aizada Dayrabaevna (Modern American Journals, 2025)
The socioeconomic changes currently occurring in society are naturally pushing all sectors to new levels of development. Physical education and sports are an area of individual and collective autonomy, where a delicate balance exists between personal choice and public regulation and oversight. Physical education, as a subsystem of a comprehensive university system for training highly qualified specialists capable of achieving their potential in a highly competitive professional environment, is impossible without a healthy lifestyle, of which physical education is a necessary component. An analysis of scientific and methodological literature and a summary of the best practices of university physical education departments indicate a crisis in this academic discipline. In particular, during this period, class attendance at Volgograd universities significantly decreased, averaging 58.1% across three years of study: 58.1% at the Agricultural Academy, 63.7% at the Architectural Academy, and 65.2% at the Medical Academy. This resulted in a decline in motivation for regular physical education and sports, a decline in students' physical fitness, and a decline in their health. This alarming situation necessitated scientifically based amendments and additions to existing core physical education programs at universities, based on the development of innovative methods.